2008
DOI: 10.1677/joe-07-0505
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin inhibition at the end of lactation programs for a central hypothyroidism in adult rat

Abstract: Malnutrition during lactation is associated with hypoprolactinemia and failure in milk production. Adult rats whose mothers were malnourished presented higher body weight and serum triiodothyronine (T 3 ). Maternal hypoprolactinemia at the end of lactation caused higher body weight in adult life, suggesting an association between maternal prolactin (PRL) level and programming of the offspring's adult body weight. Here, we studied the consequences of the maternal PRL inhibition at the end of lactation by bromoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 48 publications
4
39
1
3
Order By: Relevance
“…The inhibition of the production of maternal PRL may cause obesity in progeny via this mechanism; consequently, the inhibition of the production of PRL may impair the physical capacity of the progeny, as this inhibition is associated with other metabolic and hormonal alterations (such as changes in leptin levels and insulin resistance). Furthermore, the inhibition of the production of maternal PRL at the end of lactation induces a hypothyroidism in 180-day-old adult offspring (Bonomo et al 2008) that is related to low physical capacity (Zarzeczny et al 1996, Casimiro-Lopes et al 2008. However, previous work from our laboratory showed that animals in this model had higher exercise capacity at 90 days; this capacity returned to control levels at 180 days, even in animals with higher levels of VFM during both periods.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The inhibition of the production of maternal PRL may cause obesity in progeny via this mechanism; consequently, the inhibition of the production of PRL may impair the physical capacity of the progeny, as this inhibition is associated with other metabolic and hormonal alterations (such as changes in leptin levels and insulin resistance). Furthermore, the inhibition of the production of maternal PRL at the end of lactation induces a hypothyroidism in 180-day-old adult offspring (Bonomo et al 2008) that is related to low physical capacity (Zarzeczny et al 1996, Casimiro-Lopes et al 2008. However, previous work from our laboratory showed that animals in this model had higher exercise capacity at 90 days; this capacity returned to control levels at 180 days, even in animals with higher levels of VFM during both periods.…”
Section: Discussionmentioning
confidence: 85%
“…In the first model, we used a pharmacological approach to inhibit the production of maternal prolactin (PRL) with the dopamine agonist bromoa-ergocryptine (Bro). This method programs for obesity, hyperleptinemia, leptin resistance (Bonomo et al 2007), and hypothyroidism (Bonomo et al 2008), and symptoms (including insulin resistance and an altered lipid profile) are similar to those of metabolic syndrome (Moura et al 2009). More recently, we obtained a similar profile in adult animals with a non-pharmacological model where a maternal bandage was used to cover the teats of the dam in the late lactation, thus also inducing an early weaning of offspring (Lima et al 2011(Lima et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Desse modo, o desmame precoce e a consequente privação desses compostos presentes no leite materno podem ter influência sobre o risco de desenvolver obesidade na idade adulta [21][22][23][24][25] . Apesar de o efeito protetor do aleitamento materno em relação à adiposidade ser biologicamente plausível, os resultados obtidos em estudos epidemiológicos são inconsistentes.…”
Section: N T R O D U ç ã Ounclassified
“…Uma vez que o consumo de ração não diferiu entre os grupos, a diferença observada na massa corporal entre os animais amamentados e os animais desmamados precocemente pode ser atribuída à presença de fatores não nutricionais presentes no leite materno, a exemplo da leptina e do EGF, bem como a diferenças na resposta endócrina à alimentação (insulinemia pós-prandial) [15][16][17][18][19][20][21][22][23][24][25] . Nesse contexto, Attig et al 24 observaram que o tratamento com um antagonista da leptina entre o 2º e o 13º dia de vida resultou em um aumento significante do peso e da gordura corporal em ratos adultos.…”
Section: I S C U S S ã Ounclassified
See 1 more Smart Citation